Neurodydaktyka i nauka poprzez zabawę grupową (Tomorrow’s school? Tradition and (r)evolutions in education, 2023)
The aim of the article is to show the possibilities of combining education with an environment friendly to modern students. Learning through group play, using various scientific discourses, becomes more effective and practical. This paper presents examples of Polish lessons in primary school, analyzing the literary text with the use of musical and artistic materials, as well as exercises developing creativity and the ability to work in teams.